Theoretical and Experimental Study of Composite Beams - Jan Bujnak; Monika Simalova (Communications - Scientific letters of the University of Zilina, 1999)
The paper discusses the traditional structural analysis of composite structures and actual limit-state design as well as the efficient elasto-plastic computer model. The results of the alternative analytical study are compared with test results on the composite beam specimens.